Structural basis of GTPase-mediated mitochondrial ribosome biogenesis and recycling - Hauke S. Hillen (Nature Portfolio, 2021)
Maturation of the ribosomal peptidyl transferase center (PTC) is mediated by universally conserved GTPases. Here, cryo-EM structures of mitochondrial ribosomal large subunit assembly intermediates and of mature ribosomes offer insight into the roles of several assembly factors, including GTPBP6’s role in both ribosome biogenesis and recycling.